Analisis Kinerja Keuangan Perusahaan Dengan Menggunakan Metode Perhitungan Economic Value Added (EVA) Pada Perusahaan Manufaktur - Ary Fiyanto; Indra Setiawan Purba; Hugo Aries Suprapto; Sandy Mahardhika (Peneliti.net, 2022)
The analysis that is generally done in measuring the company's financial performance is the analysis of financial ratios by measuring the level of liquidity, activity, solvency, and profitability. There is another way to measure it. Financial performance measurement can be used using the Economic Value Added (EVA) method. This research method uses quantitative methods, with a descriptive approach. This research was conducted by collecting, processing, simplifying, presenting, analyzing financial statements and knowing the company's financial performance by using the Economic Value Added (EVA) calculation method in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange in 2015 – 2019. The results of all calculations for 2015-2019 at PT Champion Pacific Indonesia Tbk do not all show an EVA value above 0, it can be seen that in 2018 the calculation results at PT Champion Pacific Indonesia Tbk show an EVA value below 0. This means that in 2018 the rate of return generated by the company This condition is lower than the level of cost or rate of return demanded by investors. This situation indicates that the value of the company is reduced (destroy value).